Sivananda beginner's guide to yoga - Sivadasananda (London : Gaia Books, 2006)
The vast technological progress that has been made in recent decades has resulted in the pace of our lives becoming tremendously fast. Stress relief is therefore the number one reason for the practice of yoga today. The simplicity of practising yoga on a small mat on the floor offers an all-too-welcome contrast to the complexity of modern life, gradually allowing the body and mind to regain their balance.
Include index.
Keywords: Exercise & workout books